2020
DOI: 10.1002/qua.26439
|View full text |Cite
|
Sign up to set email alerts
|

Can doping of transition metal oxide cathode materials increase achievable voltages with multivalent metals?

Abstract: Density functional theory computations reveal how p-doping of transition metal oxide cathodes could increase voltages of multivalent batteries.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…An important observation we make is that the formation of oxygen dimers is favorable in the presence of cation vacancies and oxygen interstitials. The oxygen dimerization phenomenon has previously been predicted to occur upon the insertion of excess holes in BiVO 4 , TiO 2 , and SrTiO 3 as well as other transition-metal oxides when subjected to extrinsic doping. , Ambrosio and Wiktor found that the presence of such dimers at the surface of bismuth vanadate leads to a more favorable energy alignment to the redox level associated with oxidation of hydroxyl ions, a crucial step of the water-splitting reaction, and stabilizes the surface in alkaline conditions . While the effect of the defects in the vicinity of the dimer remains to be seen, treating BiVO 4 to favor the formation of cation vacancies or oxygen interstitials and, thereby, oxygen dimer formation could be a new avenue for improving the PEC efficiency and stability of the material.…”
Section: Discussionmentioning
confidence: 96%
“…An important observation we make is that the formation of oxygen dimers is favorable in the presence of cation vacancies and oxygen interstitials. The oxygen dimerization phenomenon has previously been predicted to occur upon the insertion of excess holes in BiVO 4 , TiO 2 , and SrTiO 3 as well as other transition-metal oxides when subjected to extrinsic doping. , Ambrosio and Wiktor found that the presence of such dimers at the surface of bismuth vanadate leads to a more favorable energy alignment to the redox level associated with oxidation of hydroxyl ions, a crucial step of the water-splitting reaction, and stabilizes the surface in alkaline conditions . While the effect of the defects in the vicinity of the dimer remains to be seen, treating BiVO 4 to favor the formation of cation vacancies or oxygen interstitials and, thereby, oxygen dimer formation could be a new avenue for improving the PEC efficiency and stability of the material.…”
Section: Discussionmentioning
confidence: 96%
“…It has been previously established that the magnitude of U necessary to reproduce the correct reaction thermodynamics of vanadium oxides is significantly smaller using a localized basis set in SIESTA, the setup used in this work, than what is commonly reported with plane-wave codes . It was found that uncorrected GGA functionals already deliver reliable formation energies and a qualitatively correct electronic structures using a localized basis and pseudopotentials . For this reason, we mainly employed the uncorrected PBE GGA functional in this work.…”
Section: Methodsmentioning
confidence: 98%
“…32 It was found that uncorrected GGA functionals already deliver reliable formation energies and a qualitatively correct electronic structures using a localized basis and pseudopotentials. 33 For this reason, we mainly employed the uncorrected PBE GGA functional in this work. We were able to match the experimentally reported crystal structures of both phases and their energetic ordering with reasonable accuracy as can be seen in Table S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%